Microorganisms cells destruction by mechanical method: justification of research relevance - Hrininh-Hera, Kateryna; Omelianenko, Kostiantyn; Gubenia, Oleksii; Avramia, Ionut (My University, 2023)
There are assumptions that the topic of destruction of cells and tissues on an industrial scale is relevant. This topic is not sufficiently disclosed in the literature. Before carrying out a scientific project on the cells destruction, this topic relevance should be substantiated. The topic microorganisms cells destruction by the industrial methods is relevant. The tasks are to substantiate the advantages and disadvantages of bead mills, to determine the influence of process parameters on productivity and quality, to establish the kinetics of cell destruction.
Keywords: cell disruption; bead mill; руйнування клітин; бісерний млин; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв